2005
DOI: 10.1097/01.ico.0000141235.26096.1d
|View full text |Cite
|
Sign up to set email alerts
|

Candidate Gene Screening for Posterior Polymorphous Dystrophy

Abstract: None of the 12 probands with PPCD demonstrated the previously described Gly160Asp mutation within the VSX1 gene. The Asp144Glu missense change, present in an affected patient as well as an unaffected control individual, appears to be a rare polymorphism, not a disease-causing mutation. No coding region changes were identified in the ID1 or BCL2L1 genes. Therefore, although we report a number of novel polymorphisms in the VSX1 and ID1 genes, the failure to identify any sequence variants that sort with the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 11 publications
(13 reference statements)
0
20
1
Order By: Relevance
“…Mutations in a visual system homeobox gene 1 (VSX1; MIM# 605020) within the original linked interval were implicated as disease causing in some PPCD patients (Heon, et al, 2002;Valleix, et al, 2006). However, this finding was not confirmed by other reports which excluded VSX1 by linkage analysis and by direct sequencing (Gwilliam, et al, 2005;Aldave, et al, 2004). Linkage data indicates that there is another, as yet unidentified, PPCD1 gene on chromosome 20p11.2 (Gwilliam, et al, 2005).…”
Section: Introductioncontrasting
confidence: 42%
“…Mutations in a visual system homeobox gene 1 (VSX1; MIM# 605020) within the original linked interval were implicated as disease causing in some PPCD patients (Heon, et al, 2002;Valleix, et al, 2006). However, this finding was not confirmed by other reports which excluded VSX1 by linkage analysis and by direct sequencing (Gwilliam, et al, 2005;Aldave, et al, 2004). Linkage data indicates that there is another, as yet unidentified, PPCD1 gene on chromosome 20p11.2 (Gwilliam, et al, 2005).…”
Section: Introductioncontrasting
confidence: 42%
“…The p.D144E variant was previously reported as disease causing in two affected family members with PPCD1 and keratoconus, 23 but has been detected in healthy controls 56 and glaucoma probands, 23 as well as in keratoconus patients. 29,35,47 In the cases with p.D144E reported by Bisceglia et al 35 from keratoconus families, one case was effectively a sporadic patient and in the second family in which segregation was reported, three out of the four affected patients had a diagnosis of forme fustre or subclinical keratoconus.…”
Section: Discussionmentioning
confidence: 96%
“…The VSX1 gene located within 20p11.21 of the candidate gene region for keratoconus and several pathogenic mutations in VSX1 gene were also found in various corneal dystrophies such as keratoconus and posterior polymorphous corneal dystrophy (PPCD, MIM122000) (Aldave 2005;Aldave et al 2005;Heon et al 2002). Heon et al (2002) identified mutations in the VSX1 homeobox gene in patients with either keratoconus or PPCD.…”
Section: Discussionmentioning
confidence: 99%